Desain Solar Tracking Dual Axis Berbasis Arduino dan Sensor Light Dependent Resistor untuk Meningkatkan Daya Keluaran Sel Surya - Hasyim Asyari; Aan Wisnu Aji (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2023)
Photovoltaic is a semiconductor technology that is used to convert or convert sunlight into electrical energy. The intensity of sunlight is one of the dominant factors for generating electrical energy, so efficiency will increase when the surface of the photovoltaic or solar cell always faces the direction of the sun's rays. In real terms, the position of the arrival of sunlight is always changing because the earth rotates, so that the increase in the production of electrical energy is sought by solar panels to move according to the direction of the sun's rays. The purpose of this research is to design a dual axis tracking that is able to position the photovoltaic to always get the maximum sunlight automatically, as an effort to increase the production of electric power in photovoltaic. The research method consisted of several stages, namely the use of 2 solar cells with a capacity of 120 Wp each and photovoltaic installation, hardware design with dual axis, Arduino-based software development, and the final stage was system testing. The test results show that the average electric power generated by solar cells with dual axis solar tracking is around 1.3 times greater than that of non-solar tracking solar cells. The highest electric power produced by solar cells with solar tracking and non-tracking is 49,28 Watt and 37,66 Watt respectively.